Fiscal Stimulus with Spending Reversals - Gernot J. Müller; Giancarlo Corsetti; André Meier (Verein für Socialpolitik, 2010)
The impact of fiscal stimulus depends not only on short-term tax and spending policies, but also on expectations about offsetting measures in the future. This paper analyzes the effects of an increase in government spending under a plausible debt-stabilizing policy that systematically reduces spending below trend over time, in response to rising public liabilities. Accounting for such spending reversals brings an otherwise standard new Keynesian model in line with the stylized facts of fiscal transmission, including the crowding-in of consumption and the 'puzzle' of real exchange rate depreciation. Time series evidence for the U.S. supports the empirical relevance of endogenous spending reversals.
Keywords: E61; E63; F41; 330; Fiscal policy transmission; consumption; real exchange rate; real interest rates; sticky prices; monetary policy